Including disabled people in poverty reduction work : 'Nothing about us, without us' - Yeo, Rebecca (2003)
Argues that the exclusion of disabled people from international development organizations and research reflects and reinforces the disproportinately high representation of disabled people among the poorest of the poor. Review the ways in which different institutions challenge poverty and esclusion among disabled people. Presents survey evidence of the limited inclusion of disabled people within development institutions and policies.